The impact of degree field on the earnings of male and female college graduates - Freeman, Catherine E.; Snyder, Thomas D.; Connolly, Brooke (Education Policy Analysis Archives, 2005)
Since the gender demographics across majors have dramatically changed over the last few decades, a re-examination of the relationship between gender, undergraduate major selection, and compensation levels once in the workforce is important. This article will focus on how the salaries of college graduates have changed over the last decade. The analyses will explore the extent to which undergraduate major selection contributes to any male-female salary gap. A comparison of regression models for 1993 and 2001 describes the extent to which the selection of major remains a significant factor among those individuals who have entered the workforce.